Gamification in the process of cognitive stimulation in children with Down syndrome - Navas-Alarcón, Eduardo (2023)
This research studies the use of new information and communication technologies for the benefit of children with Down syndrome, it is about the design and programming of an application for mobile devices that stimulates playful interactions with the resource of gamification that takes advantage of the technological potential of video games in the educational field. Its interface was designed using Adobe Animate software with Action script programming language, designing two-dimensional animated graphics that encourage affective, cognitive and behavioral processes such as animals, their habitat and food; it also incorporates scenarios and sounds of easy grouping to encourage their academic activity in attention, visual retention and cognitive stimulation. The methodology used to design the first prototype was a survey of teachers, psychologists and language specialists of the Foundation for children with special abilities "San Miguel de Salcedo" FUNESAMI, who actively contributed in the development, structure, content and implementation of the application, which was evaluated with the active participation of 14 children with Down syndrome in average age of 6 to 12 years, The application was evaluated with the active participation of 14 children with Down syndrome with an average age of 6 to 12 years, finding remarkable improvements in the attention and retention that the child directs to the game, achieving an interaction that facilitates the teaching-learning process compared to the traditional method, thus contributing to the improvement of the quality of life and development of the child patient, thus complying with what is stated in the Constitution of Ecuador contributing to the good living.